Ginsenoside compound K-based multifunctional liposomes for the treatment of rheumatoid arthritis - Meng Zhang; Ru Zhang; Chunbo Feng; Xinnan Jiang; Xinchun Xu; Jianxin Wang (Drug Delivery)
The clinical treatment of rheumatoid arthritis (RA) with first-line therapeutic drugs is hindered by the poor solubility, low bioavailability, off-target toxicity, and insufficient accumulation in inflamed joints. Liposomes have been shown to mitigate some of these limitations in drug delivery systems. However, the use of cholesterol to stabilize liposomal structures remains controversial due to its potential association with cardiovascular diseases. Here, we developed a novel liposome based on ginsenoside compound K (CK), which not only serves as an effective therapeutic agent for RA but also replaces cholesterol as a membrane stabilizer to address these challenges. Compared with conventional liposomes, ginsenoside CK Liposomes (CK@Lipo) are excellent nanoparticles, with CK stabilizing the liposomal structure and providing targeting functionality toward inflamed joints. When encapsulated with dexamethasone (Dex), CK@Lipo exhibits a synergistic anti-inflammatory effect, slowing the progression of RA. This study provides a theoretical basis for the future development of multifunctional novel ginsenoside CK@Lipo.